The role of school management as democratic school leadership (Research, Society and Development, 2020)
This article has as its theme The Role of School Management as Democratic School Leadership. In view of the school routine, the function of the director often ends up dispersing and, therefore, knowledge about his real duties is essential to guarantee the quality of the educational process in all its dimensions. The objective was to understand the role of the manager in relation to his duties vis-à-vis the school community. For this, we carried out a qualitative research and resorted to bibliographic research, where we researched academic authors who address democratic management, such as Gadotti (2004), Rios (2010), Teixeira (2003), Lück (2004) and Libâneo (2005 ) among others that refer not only to the democratic process, but also to the role of the manager, his leadership and educational administration. This theoretical foundation supported our analysis and reflections on the specific function of the school manager. Therefore, we conclude how much it is necessary to understand the school manager's duties, as well as the relevance of his work being directed and dynamized through dialogue and collective work. Thus, in addition to the fact that there is no distribution of inappropriate functions to each professional, there will be no work overload and it will be possible, when carrying out both administrative and pedagogical functions, to guarantee the quality of the school's educational process.